Trends and Transitions in Silicate Weathering in the Asian Interior (NE Tibet) Since 53 Ma - Yang, Yibo; Han, Wenxia; Ye, Chengcheng; Galy, Albert; Fang, Xiaomin (Frontiers in Earth Science, 2022)
The relationship between silicate weathering, Tibetan Plateau uplift, and global cooling during the Cenozoic provides a valuable case study for understanding the interaction of tectonics and climate. The Tibetan Plateau uplift is considered to have caused Cenozoic cooling via the atmospheric CO2 drawdown by increased silicate weathering. However, this hypothesis has been intensively debated over the past few decades due to the lack of complete silicate weathering records from the continental interior, which can directly track the effects of uplift on weathering. We provide the first complete long (past 53 Myr) continental silicate weathering record from the NE Tibetan Plateau, combined with a comprehensive analysis on its evolution pattern, critical transitions, and associated driving forces. The silicate weathering intensity in NE Tibet is characterized by a long-term Paleogene decrease, modulated by global cooling, and a Neogene increase that may be related to the East Asian summer monsoon (EASM) intensification. Three major system transitions in regional silicate weathering are identified at ~26-23 Ma, ~16 Ma and ~8 Ma, which are linked to enhanced EASM forced primarily by tectonic uplift at these intervals, with some surbordinate influences from global climate at ~16 Ma. We also capture an intensification of the 100-kyr cycle at ~16 Ma and ~8 Ma in the obtained silicate weathering record, which is in coincidence in time with the enhancement of the EASM. This might suggest some contribution of the Antarctic ice sheets on modulating the regional silicate weathering in the NE Tibetan Plateau on a timescale of 105-106 years, through its influences on the EASM as proposed by previous studies.